Analyzing the effect of interference on the utilization of French in ivory coast: social and linguistic aspects (Revista de Investigaciones Universidad del Quindío, 2022)
The current study intends to recognize the various sorts of interference in French in Ivory Coast, a West African nation. The current article mainly concentrates on a propound examination and investigation of the linguistic procedure that demonstrates itself in the survey in the impression of Ivorian native tongues and a complicated range of elements and factors. This study focuses on the impacts of grammatical, phonetic, and lexical interference, occurring to various levels on basilect and mesolect French variants and are not in line with the French speech norms in France. The methodology is on the basis of investigating the cases of grammatical, phonetic, and lexical interference, revealing the particular characteristics of Ivorian French. Based on the analysis, lexical interference tends to be clear in alterations in the meaning of the original lexeme and the words borrowing from Ivorian tongues, exposing cultural realities. Based on that, grammatical and phonetic interference is greatly pronounced in the tongue of basilect-dominant talkers.
Keywords: Ivory Coast; language contact; indigenous languages; French; interference